AMB Express - Steinbüchel, Alexander
AMB Express is a high quality journal that brings together research in the area of Applied and Industrial Microbiology with a particular interest in 'White Biotechnology' and 'Red Biotechnology'. The emphasis is on processes employing microorganisms, eukaryotic cell cultures or enzymes for the biosynthesis, transformation and degradation of compounds. This includes fine and bulk chemicals, polymeric compounds and enzymes or other proteins. Downstream processes are also considered. Integrated processes combining biochemical and chemical processes are also published.